SUN-582 Effect of the Combination of Conjugated Estrogens and Bazedoxifene on Muscle and Serum Lipidome in Obese Postmenopausal Women: A Placebo-Controlled Randomized Pilot Trial - Lovre, Dragana (J Endocr Soc, 2020)
Background and Objectives: Menopause is characterized by estrogen deficiency and predisposes women to weight gain and metabolic disturbances including lipid abnormalities. Orally-administered estrogens increase high-density lipoprotein (HDL) and triglycerides (TG) cholesterol and decreases low-density lipoprotein (LDL) cholesterol levels. The increase in serum TGs is not well understood. The objective of this study was to assess the effect of CE/BZA on serum and skeletal muscle lipid species in obese postmenopausal women. Methods: Randomized double-blind crossover pilot trial in 8 obese postmenopausal women (53± 3 years, BMI 35.7±3.2 kg/m(2)) assigned to 8 weeks of CE/BZA or placebo with 8 weeks washout in between. At the end of each 8-week treatment period, intrahepatic and skeletal muscle lipids were measured by proton magnetic resonance spectroscopy ((1)H-MRS) while serum and skeletal muscle lipidomics were assayed by ultrahigh performance liquid chromatography/mass spectrometry (UHPLC/MS). Results: No treatment differences were observed in intrahepatic lipid, soleus intramyocellular lipid (IMCL) or extramyocellular lipid (EMCL) as well as tibialis anterior IMCL or EMCL. The serum metabolome and lipidome comprised a total of 2002 biochemicals. Treatment with CE/BZA was associated with higher levels of diacylglycerols (DAGs) and triacylglycerols (TAGs) composed of long-chain saturated fatty acids (SFA, palmitic C16:0 and arachidic C20:0), monounsaturated FAs (MUFA, palmitoleic C16:1, oleic C18:1 and ecosenoic C20:1), and polyunsaturated FAs (PUFA, linoleic C18:2, arachidonic C20:4, eicosapentaenoic C20:5, and docosahexaenoic C22:6) compared to placebo (all p<0.05). Treatment with CE/BZA was also associated with lower levels of several acylcarnitine species, which are markers of FA oxidation, including long-chain SFA (C14, C16 and C18), MUFA (C18:1 and C24:1) and PUFA (C18:2, C20:2 and C20:4). In addition, treatment with CE/BZA was associated with higher levels of phosphatidylcholines (PCs), phosphatidylinositols (PIs), phosphatidylethanolamines (PEs), sphingomyelins (SMs), and ceramides (CER), as well as lower levels of lysophophatidylcholines (LPCs). There were no treatment differences in carnitine or ketones levels. The skeletal muscle analysis comprised a total of 652 biochemicals, but unlike in serum, no significant treatment differences were observed in the skeletal muscle lipidome. Conclusions: Our lipidomic analysis supports a model in which CE/BZA (and likely all oral estrogens) increases hepatic de novo FA synthesis and esterification into TAGs for export into TAG-rich very low-density lipoproteins, as well as decreased FA oxidation, respectively. Although CE/BZA treatment inhibits FA oxidation, it is not associated with hepatic lipid accumulation as measured by MRS, or skeletal muscle lipid accumulation measured by MRS and lipidomics.